Caryochroite, a new heterophyllosilicate mineral species related to nafertisite from the Lovozero massif (Kola Peninsula, Russia) - KARTASHOV P. M; SOBOLEVA S. V; CHUKANOV N. V.; FERRARIS, Giovanni (Mineralogical Association of Canada:Cityview 78087, Meriline Pos Outl, Ottawa Ontario K2E 1B1 Canada:(613)226-4651, EMAIL: canmin.mac.ottawa@sympatico.ca, INTERNET: http://www.mineralogicalassocaition.ca, Fax: (613)226-4651, 2006)
Caryochroite, ideally (Na,Sr)3(Fe3+,Mg)10[Ti2Si12O37](H2O,O,OH)17, is monoclinic with cell parameters a 16.47, b 5.303, c 24.39 Å, β 93.5º; Z = 2. It was collected in dumps of the Umbozero mine (Mount Alluaiv, Lovozero massif, Kola Peninsula, Russia) and is associated with albite, elpidite, epididymite, quartz, natrolite, pyrite, galena, sphalerite and bitumen. Caryochroite is the product of supergene alteration of an unidentified Fe2+-rich protophase and forms centimetric crusts. Physical properties: submicrometric 001 lamellae, [010] elongate; opaque; hazel-brown colour; pale brownish-yellow streak; dull to waxy lustre; hardness, 2.5; good 001 cleavage; Dmeas 2.990; biaxial (-), α < 1.700, β 1.745, γ 1.775, 2Vmeas 75º; pleochroism, X = Y (dark brown) > Z (brown). The name refers to the colour. Chemical data from electron microprobe, wet analysis for Fe and thermal analysis (9.17 wt % loss at 800o C); Mössbauer spectroscopy shows major Fe3+ and minor Fe2+; empirical formula, (Na1.19Sr0.62Ca0.41Mn0.35K0.26)Σ2.83(Fe3+7.98Mg1.15Mn0.49Fe2+0.38)Σ10.00(Ti1.87Fe3+0.13)Σ2.00 (Si11.74Al0.26)Σ12.00 O54.10H20.40. Spacing (Å) and intensity (%) of the strongest lines of the X-ray powder-diffraction pattern: 14.1(20), 13.3(30), 12.1(100), 4.38(10), 2.692(12), 2.631(13). Cell parameters, X-ray powder-diffraction pattern, chemical composition and infrared spectrum suggest that caryochroite is the second heterophyllosilicates based on a nafertisite-type HOH layer. The role of caryochroite and associated titano- and zirconosilicates as catalysts of bitumen formation in situ is discussed.